Economic Load Dispatch of Three Bus Thermal Generator Using Fuzzy Logic Technique - Kulkarni, Dharati; Gaded, Kishore Kumar; Ajay Nagendra, B. S.; Koushik, Karthik S.; Prabhu, Kavya (Asian Journal of Electrical Sciences, 2019)
This paper gives details/information about economic load dispatch using manual method and optimized fuzzy method. Using manual method, we get lambda ‘λ’ one of the inputs to the fuzzy by using different demand values. The calculations of manual method and fuzzy results are both mentioned in this paper. The whole analysis is done considering transmission losses.